Impact of National Health Policies on Maternal and Child Health Education Programs among Residents in Dutsin-Ma, Katsina State, Nigeria (Federal University Gusau Faculty of Education Journal, 2026)
This paper is investigated the impact of national health policies on maternal and child health education programs among residents in Dutsin Ma, Katsina State, Nigeria. The vulnerability and developmental needs of maternal and children health education programs in Nigeria necessitated the enactment of National Health Policies. However, there have been concerns about the effectiveness of this policy. This study investigated public perception on the performance of National Health Policies and healthcare for maternal and children in Dutsin ma Area of Katsina State. The study adopted mixed methods of data collection through questionnaire and In-depth Interviews. Using multistage, probability and stratified sampling techniques, the study selected 460 respondents from households, children, caregivers, educators and health workers. The social attachment theory anchored the theoretical explanation. The hypotheses were tested using logistic regression through the statistical package for social sciences version 27. The study revealed a pseudo-R² of 0.09 (χ² = 7.84, df = 6, p > 0.05), indicating no significant improvement in maternal and child healthcare. Respondents reported low satisfaction with policy implementation in the study area, citing irregular immunizations, inadequate health screenings, limited skilled birth attendants, weak nutritional interventions, under-resourced facilities, hidden cost and poor service delivery. The study recommended a review of antenatal screening programmes, deploying skilled birth attendants at all hospitals, strengthening immunization logistics, revitalizing breastfeeding campaigns, and improving coordination of nutritional interventions to enhance policy effectiveness and child health outcomes in study area.